Acute effect of resisted sprinting upon regular sprint performance - van den Tillaar, R.; Teixeira, A.; Marinho, D. (Acta Kinesiologiae Universitatis Tartuensis, 2018)
The aim of this study was to investigate the acute effect of resisted sprinting upon running sprint performance. Thirty male athletes from track and field (age: 21.2±2.9 yrs, body mass: 69.8±9.8 kg, height: 1.75±0.08 m) performed two different test sessions (one day of 7×60 m runs alternating between regular and resisted sprinting and the other day 7×60 m of regular sprints) with 5 min between each run. Sled towing individually weighted to 10% of each participant`s body mass was used as resistance for the resisted sprints. It was found that training with or without resistance had the same effect; there is no acute effect of resisted sprinting upon sprint performance after using resisted runs. It was concluded that resisted sprinting does not have any acute positive effect upon regular sprints of 60 m, but only a fatiguing effect.